Early Childhood Exploitation: A Literature-Based Perspective on Prevention and Intervention - Anies Listyowati; Titah Kinasih (Journal of Early Childhood Education Research, 2025)
Purpose: This research examines contemporary literature perspectives on the prevention and management of early childhood exploitation. Despite growing global attention to child protection, there remains a critical need to synthesize evidence-based approaches that effectively address various forms of exploitation affecting young children. This study aims to identify the most prevalent forms of exploitation, evaluate current prevention and intervention strategies, and provide evidence-based recommendations for comprehensive child protection programs. The significance lies in its systematic analysis of recent literature to inform policy and practice in safeguarding vulnerable children. Methodology: A systematic literature review was conducted analyzing scientific articles published between 2018-2023. Data were retrieved from leading electronic databases using predefined inclusion criteria. A total of 48 selected articles were systematically reviewed and analyzed to identify patterns in exploitation types, prevention strategies, intervention programs, and their effectiveness. Thematic synthesis was employed to categorize findings and assess evidence quality across different protection approaches and contexts. Results : The analysis identified five primary forms of early childhood exploitation: labor exploitation (43%), sexual exploitation (27%), early marriage (18%), exploitation in armed conflict (7%), and online exploitation (5%). Multisectoral programs integrating educational, economic, and legal aspects demonstrated highest effectiveness. Comprehensive trauma recovery programs showed 73% success rate in short-term outcomes, while school-based education (68%) and family strengthening programs (42%) proved effective for long-term prevention. Technology-based solutions offered innovative approaches but faced challenges including data privacy concerns, digital divide, and sustainability issues. Effective policy reform requires strong political commitment, rights-based approaches, and clear accountability mechanisms. Conclusions: This research underscores the importance of evidence-based, multisectoral approaches in preventing and managing early childhood exploitation. Findings highlight the necessity of local contextualization and active child participation in developing protection programs. Future interventions should integrate comprehensive support systems addressing immediate trauma recovery while strengthening families and educational institutions for sustained prevention. Policymakers must prioritize child rights, ensure intersectoral collaboration, and leverage technology responsibly to create effective and sustainable child protection systems.